A probabilistic model of the impact of cultural participation on social capital. Issue 2 (3rd April 2021) - Sakalauskas, Leonidas; Dulskis, Vytautas; Lauzikas, Rimvydas; Miliauskas, Arunas; Plikynas, Darius
ABSTRACT: This study attempts to construct a computer-based probabilistic model of the social impact of cultural events, which may be useful for simulating and measuring social impact in a community context. Changes in social capital as a result of actors' participation in cultural events are modeled, assuming that links exist between cultural participation and social capital measured using the methodology of the Organization for Economic Co-operation and Development. The computer-based probabilistic model for simulation of the social impact of a cultural event flow is developed, and the model for a social impact assessment using statistical socio-cultural data is given. Finally, verification of the developed model is carried out by Monte Carlo-based computer-simulated case study, and the example of application to statistical cultural participation data is presented.